Bo at Iditarod Creek - Hill, Kirkpatrick; Pham, LeUyen (New York : Henry Holt and Company, 2014)
In 1920s Alaska, when five-year-old Bo and her two adoptive fathers move to Iditarod Creek to work at a new gold mine, Bo feels homesick until she realizes there is friendship to be found everywhere--and Iditarod Creek may hold some surprises for her already unconventional family.
Sequel to: Bo at Ballard Creek.
Keywords: Alaska -- History -- 1867-1959 -- Juvenile fiction; Families -- Alaska -- Juvenile fiction; Adoption -- Juvenile fiction; Moving, Household -- Juvenile fiction; Family life -- Alaska -- Fiction; Adoption -- Fiction; Moving, Household -- Fiction